2013
DOI: 10.1166/mex.2013.1104
|View full text |Cite
|
Sign up to set email alerts
|

Presence of stable carbon centric free radicals and ferromagnetic elements in the antennae and the wings of nocturnal silk moth: A magnetic nanostructure for magneto sensing

Abstract: This work addresses an interesting, interdisciplinary problem of nature-"the mechanism by which animal senses the earth's magnetic field and navigate". Currently there are two existing theories trying to explain, "How the animal senses the magnetic field of earth". One theory is based on the presence of biogenic magnetic materials in the body of the animals. Such magnetic materials which are present inside the body, orients itself according to the earth's weak magnetic field and convey the information to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Such type of carbon-centric free radicals are very stable in nature and extremely difficult to reduce or oxidize. Anthropogenic multi-walled carbon nanotubes trapped in spider web and antennae of the silk moth preserves such pool of carbon-centered free-radicals for a long period of time and exhibit soft magnetic behavior 13 14 . Thus EPR measurements indicate the presence of soft ferromagnetic elements and a pool of carbon-centered free radicals in the cocoon membrane ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such type of carbon-centric free radicals are very stable in nature and extremely difficult to reduce or oxidize. Anthropogenic multi-walled carbon nanotubes trapped in spider web and antennae of the silk moth preserves such pool of carbon-centered free-radicals for a long period of time and exhibit soft magnetic behavior 13 14 . Thus EPR measurements indicate the presence of soft ferromagnetic elements and a pool of carbon-centered free radicals in the cocoon membrane ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to pinpoint the exact organic moiety in the silk fiber structure of cocoon, which possibly exhibits carbon centric free radical features. Since silk thread in cocoon is a super-coiled structure forming a rigid matrix, it may lead to ‘frustrated spin’ in several carbon moieties and such ‘frustrated spin on carbon’ leads to ‘carbon centric free radicals’ 13 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Scientists found that many sources of directional information can contribute to birds' navigation, such as landmarks or topographic features [58,59], stars [60][61][62][63][64], the sun [65][66][67], and so on. Among these sources and hypotheses, magnetite as well as biochemical radical-pair reactions has been hypothesized to mediate sensitivity to Earthstrength magnetic fields through fundamentally different physical mechanisms [68,69].…”
Section: Chemical Compass In Birds 21 Introductionmentioning
confidence: 99%
“…the sun [65][66][67], and so on. Among these sources and hypotheses, magnetite as well as biochemical radical-pair reactions has been hypothesized to mediate sensitivity to Earthstrength magnetic fields through fundamentally different physical mechanisms [68,69].…”
Section: Introductionmentioning
confidence: 99%